A Review of Microfiltration Membrane in Separating Folic Acid from Fermented Dark Green Leafy Vegetables (DGLVs), Legumes, Beans, and Cereal for Nutraceutical Application - ., Aspiyanto; Susilowati, Agustine; Melanie, Hakiki; Maryati, Yati (International Journal of Membrane Science and Technology, 2023)
DGLVs (spinach, broccoli), legumes (soybean, mung bean, kidney bean), and cereal (corn) are well recognized for human health benefits due to the presence of natural folate (vitamin B9) with essential micronutrients. Folate is among the most unstable vitamins for the normal functions of the human body. The recent development of membrane-based methods for the separation of folic acid (FA) is reviewed from the selected literature and covers the result of significant research that has been performed in the last five years on the use of the microfiltration (MF) method. This is coupled with the fermentation process to support and achieve separation or recovery of FA from their selected plant-based food source. The nixtamalization, fermentation, separation, and purification of DGLVs, legumes, and beans, as well as corn, were conducted using the MF (pore size 0.15 µm) membrane separation method. The results showed that the MF membrane was able to separate FA components in permeate from fermented spinach and broccoli, soybean, mung bean, kidney bean, and corn, namely 7.14 and 3.79, 197.00, 325.37 and 242.93, and 121.10 µg/mL, respectively. Meanwhile, FA content in retentate from fermented spinach and broccoli, soybean, mung bean, kidney bean, and corn was 58.90 and 28.10, 362.07, 254.07 and 506.07, and 212.84 µg/mL, respectively. The applications of membrane techniques were used as an alternative to some unit operations in the solving of separation issues as well as the development of selected new fermented plant-based food sources. The contemporary pressure-driven membranes, such as MF, and the main applications were related to pre-treatment, selected fermented plant-based food sources, and alternative technology for extending the shelf life of natural folate. The utilization of MF membranes in the nutraceutical field holds significant promise, particularly in the creation of value-added products from minor compounds.